A feasibility study on the production of sulfuric acid from pyrite roasting - De La Vega, Sandi D.; Doroja, Gian Carlo H.; Leoncito, Patrick Jan M.; Pizarro, Rochelle Q.
Sulfuric acid is one of the largest produced chemicals in the world in terms of volume and 60% of its consumption is from the phosphate fertilizer industry. The most commonly used process in the production of sulfuric acid is the burning of elemental sulfur. Another process uses pyrite which is a cheaper raw material compared to elemental sulfur. Being one of the most common sulfide mineral containing 53% sulfur, pyrite then is seen as an alternative raw material for sulfuric acid production. Using pyrite as its raw material in the production of sulfuric acid, Pyrite Chemicals offers Gold Acid, a sulfuric acid of the same quality as the one available in the market but with a lower price. The market analysis determined that it is feasible to produce and sell pyritic sulfuric acid in the Philippines. The fertilizer industry, being the industry with the highest sulfuric acid demand, is the best market to target. Stiff government policies regarding fertilizer production provided the demand and supply for fertilizer manufacture in the Philippines. To promote Gold Acid, the company would establish partnerships to fertilizer manufacturers and will go directly to other users of sulfuric acid. Low prices and distinct advantages over existing commercial sulfuric acids in the market will make the product appealing to fertilizer manufacturers. The technical analysis determined that the project is technically feasible. The technology needed to produce sulfuric acid from pyrite roasting is available. All the machines required by the sulfuric acid production can be purchased from other countries. The labor needed does not require specializations that cannot be trained or hired in the Philippines. There are sufficient pyrites to last for at least 12 years to produce 350,000 MT of sulfuric acid annually. Although the Hinabangan mine has stopped operations, currently it is being rehabilitated and it will soon resume its operation. By the time the constructed plant is operational, the Hinabangan mine will be able to resume its operations. The financial analysis determined that with the proper source of financing, the project is financially feasible. The total start up cost was Php 743,253,081, with a pre-operation capital expenditure of Php 4,212,240 and a working capital of Php 23,652,323. Equity financing will be used to gain the capital needed to begin operations due to the small amount of associated costs, ease of execution, and good opportunity for expansion. The financial analysis also showed that the project was acceptable in all the ratio tests. The company performance merits its being an attractive investment to creditors, with an average rate of return of 12% and a payback period of 3.88 years. Despite the positive results determined from the market, technical, and financial analyses done, the project was determined to be socially unattractive in the social profitability analysis done. Overall, Gold Acid is market, technically, and financially feasible.